Methodological foundations of information support for decision-making in the field of food, environmental, and socio-economic components of national security - Oleh Skydan; Olga Nykolyuk; Petro Pyvovar; Pavlo Topolnytskyi (Наукові горизонти, 2023)
The negative impact of strategic threats to the development of the state in the context of the development of its national security, in particular food, environmental, and socio-economic components, has intensified in the context of Ukraine's geopolitical challenges. This issue has become particularly acute as a result of open military aggression, which makes it necessary to develop and implement a system of information support for decision-making in the field of national security of Ukraine. Therefore, the purpose of the study is to substantiate methodological foundations of information support of decision-making in the field of national security of Ukraine and their implementation within the framework of the created system, which provides for the collection of information, in particular, using space and geographic information systems, and the use of mathematical modelling and situational analysis methods for data processing. In the course of the research, methods of econometric modelling, structural and functional modelling, and spatial analysis were used. A methodological framework has been developed for decision-making support to address the problems of food, environmental, and socio-economic components of national security. A functional model and algorithm of the decision-making process in the field of national security are constructed and, based on the results obtained, a decision-making system in the field of food, environmental, and socio-economic security is developed. In addition, the study formalises the conceptual provisions of the decision-making support process in the field of national security; a procedure for modelling the country's food security indicators is proposed. Based on the proposed methodological approach, it was determined how much the area of crops decreased due to the temporary occupation and military operations, and the post-war state of fields (minelaying, destruction of crops, equipment, etc.), which allowed forming input data for further projecting of indicators of the development of the agricultural sector and food security in Ukraine, the EU, and the world. The proposed methodological provisions, algorithms, models, and the developed system can be used by state authorities to make managerial decisions on the development of policy in the areas of ensuring food, environmental, and socio-economic security of the country